The Fulfillment of Protection Rights of The Children Suffering From HIV /AIDS Disease at Semarang City - Azharistya Rahmawati; Agnes Widanti S; Suwandi Sawandi (Universitas Katolik Soegijapranata Semarang, 2019)
HIV/AIDS is one of health issues that was sensitive to talk about. It related to the unique nature of the disease. HIV/AIDS case factually appeared as an iceberg phenomenon but, in addition, it brought stigma and discrimination that were experienced by the sufferers as well as their families. The number of HIV/AIDS cases, as a matter of fact, increased every year. Although the reported number of HIV/AIDS cases of children were lower than of adults the children, anyhow, were very vulnerable to HIV/AIDS.The objectives of this research was to recognize and describe: 1. the regulations that guarantee rights protection of the children suffering from HIV/AIDS disease at Semarang City, 2. rights fulfillment of the children suffering from HIV/AIDS at Semarang City, 3. Supporting and obstructing factors influencing rights fulfillment of the children suffering from HIV/AIDS disease at Semarang City.This research applied socio-legal aproach and used analytical-descriptive specification. While The data were gathered by having interviews and observation beside library studies. The informants or data resources of this researach consisted of four children suffering HIV/AIDS and/or their guardians.The results of this research showed that there had been some legislations which mandated the guarantee of the children's rights protection. The articles of the legislations, ranging from the Constitution of 1945 to the Acts dealing with children's rights protection, had supported and strengthened each other. However, there were indeed no regulations or specific guarantee program provided to the children suffering from HIV/AIDS. Actually the rights fulfillment of the children suffering from HIV/AIDS was factually accomplsihed but it had not been optimal. The supporting factors in efforts of fulfilling the children’s rights were the the fact that there were programs of counseling and socialization of HIV/AIDS and anti-discrimination. The obstructing factor, on the other side, dealt with the budget for HIV/AIDS prevention programs that remained minimal and could not reach the whole area of Semarang City.